Analysis of the Contribution of Anthropometry and Physical Conditions to the Spike Ability of the Praporprov Volleyball Team of Semarang City in 2022 - Juliyan Syahputra Siregar; Nasuka Nasuka; Agung Wahyudi (JUARA : Jurnal Olahraga, 2023)
The purpose of this study is to analyze the contribution of anthropometry and physical condition to the spike ability of the Semarang City Praporprov Volleyball Team in 2022. The research method used is the quantitative method with a descriptive approach. This research uses survey methods and techniques, namely test and measurement techniques. A study sample of 28 athletes. The instruments studied are components of anthropometry (height, weight, arm length, leg length and sitting height) and physical condition components (strength, speed, flexibility, explosiveness, and agility) to spike ability. Research shows that 1) there is a distribution between anthropometry and spikes that is normal, and 2) there is an influence of distribution between physical conditions and regular spikes. 3) there is a positive relationship between anthropometry and spike ability with a strong relationship category 4) there is a positive relationship between physical condition and spike ability with the category of relationships that the relationship is moderate. 5) there is a contribution of influence made by anthropometry and physical condition on the spike ability of the Praporprov volleyball team in Semarang City in 2022. Conclusion There is a relationship between anthropometry and the spike ability of the Semarang City Praporprov volleyball team in 2022. There is an anthropometric contribution to the spike ability of the Semarang City Praporprov volleyball team in 2022. The physical condition contributes to the spike ability of the Praporprov Semarang City volleyball team in 2022. There is a contribution of influence made by anthropometry and physical condition on the spike ability of the Praporprov volleyball team in Semarang City in 2022.